2013
DOI: 10.1007/s00464-013-3030-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of endoscopic submucosal dissection for early gastric cancer: a single-center experience

Abstract: ESD appears to be a feasible and effective method for treating EGCs, based on the standard and expanded criteria. Close follow-up surveillance, after ESD, should be standard for all patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
87
4
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 23 publications
7
87
4
3
Order By: Relevance
“…However, diagnosis of the depth of lesions was very important. Besides, studies conducted by Yamaguchi et al [32] and Choi et al [33] showed that the expanded criteria (without undifferentiated lesions) of ESDs also had relatively higher rates of complications, which meant the conclusion of this meta-analysis was not decided by the fourth expanded criterion, that is, undifferentiated EGCs (those <1 cm) that are confined to the mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…However, diagnosis of the depth of lesions was very important. Besides, studies conducted by Yamaguchi et al [32] and Choi et al [33] showed that the expanded criteria (without undifferentiated lesions) of ESDs also had relatively higher rates of complications, which meant the conclusion of this meta-analysis was not decided by the fourth expanded criterion, that is, undifferentiated EGCs (those <1 cm) that are confined to the mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Among the remaining 19 papers, seven articles were additionally excluded because they did not compare the outcomes of EI and AI (e.g., some of them compared EMR and ESD). Finally, 12 studies were found to be appropriate for the meta-analyses [14,18,21,[24][25][26][27][28][29][30][31][32]. These studies described a total of 9635 EGC lesions: 4150 lesions the EI group and 5485 lesions in the AI group.…”
Section: Study Inclusion and Assessmentmentioning
confidence: 97%
“…ESD is recommended according to the Japanese Gastric Cancer Treatment Guidelines for the treatment of intramucosal cancer, differentiated adenocarcinoma without ulcer, and gastric tumors measuring less than 2 cm in size, affording to a feasible and effective method for treating early gastric cancers (20). ESD may carry an increased risk of failing to detect lymph node metastasis, therefore the expanded application of ESD is now under examination (21,22).…”
Section: Discussionmentioning
confidence: 99%